2022
DOI: 10.7150/thno.72676
|View full text |Cite
|
Sign up to set email alerts
|

Influences of age, race, and sex on extracellular vesicle characteristics

Abstract: Recent attention has focused on the use of extracellular vesicles (EVs) as biological indicators of health and disease. These small, nano-sized membrane bound vesicles are secreted from cells into the extracellular space and can be readily isolated from bodily fluids. EVs can carry various bioactive molecules as cargo including DNA, RNA, proteins, and lipids. These EVs can provide a snapshot of the cell of origin and a window of opportunity to assess normal physiological states as well as pathophysiological st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 80 publications
0
28
0
Order By: Relevance
“…We also reported a higher EV level of phospho-IGF-1R in women compared to men. In addition, little is known about differences in EV cargo with various demographics 35 . Here, we wanted to examine if there were differences in EV inflammatory proteins with race, sex, and poverty status.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also reported a higher EV level of phospho-IGF-1R in women compared to men. In addition, little is known about differences in EV cargo with various demographics 35 . Here, we wanted to examine if there were differences in EV inflammatory proteins with race, sex, and poverty status.…”
Section: Resultsmentioning
confidence: 99%
“…Few studies have examined whether race influences EVs 35 . Previously, we reported that there were racial differences in EV protein cargo and found higher levels of phospho-p53, total p53, cleaved caspase 3, ERK1/2 and phospho-AKT in White individuals compared to African American individuals 25 .…”
Section: Discussionmentioning
confidence: 99%
“…EVs are present in any human body fluid (plasma, urine, tears, saliva, bile, breast milk, mucus, semen, amniotic fluid, synovial fluid, cerebrospinal fluid, aqueous humor, pleural effusions, and any other secretion), and their levels reflect the delicate equilibrium between their release and clearance rates as well as the pathophysiological context. In this regard, circulating blood EVs have shown to be modulated by sex, 36 age, 37,38 exercise, 39 diet, 40 and other conditions as pregnancy 41 . Despite healthy states show presence of EVs, 42 their levels correlate with disease progression and severity, 43,44 even with the Framingham risk score 45,46 …”
Section: Leveraging Evs As Prognostic and Diagnostic Markers Of Infla...mentioning
confidence: 99%
“…A higher uptake rate could help ADMSC young -EVs produce a better protective effect. There were compressive differences in EV size, cargos and biological effects, which guided their application in the clinic, as summarized by a recent review [ 18 ]. In the analyses of NAD+ metabolism-related factors, key genes were dysregulated, except for NAMPT.…”
Section: Discussionmentioning
confidence: 99%
“…The expectation of a demographic shift to a higher elderly population structure in developed countries highlights the importance of senescence-related researches. Aging significantly influences the amount and biological function of EVs based on both clinical observations and experimental assays [ 18 ]. It has been reported that the beneficial effects of osteocyte-derived EVs diminished with aging [ 19 ], and similar outcomes were detected in MSCs [ 20 ].…”
Section: Introductionmentioning
confidence: 99%